Treatment and outcome of lung cancer in idiopathic interstitial pneumonias - Kreuter, Michael; Ehlers-Tenenbaum, Svenja; Schaaf, Miriam; Oltmanns, Ute; Palmowski, Karin; Hoffmann, Hans; Schnabel, Philipp A; Heußel, Claus-Peter; Puderbach, Michael; Herth, Felix JF; Warth, Arne (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Idiopathic interstitial pneumonias (IIP) are associated with an increased lung cancer (LC) risk. However, data on the prognostic and therapeutic impact are limited. We therefore aimed to analyze the outcome of IIP patients with LC under different treatment modalities.Methods: Patients with IIPs diagnosed in a tertiary interstitial lung diseases (ILD) center were reviewed for LC diagnosis.Results:Of 265 patients with idiopathic pulmonary fibrosis (IPF), 142 with non-specific interstitial pneumonia (NSIP), and 71 with cryptogenic organizing pneumonia (COP), 16%, 4%, and 6% were affected byLC, respectively. Patient characteristics were: IPF: 93% male, median age 67 years, forced vital capacity (FVC) 82%, diffusion capacity for Carbon monoxide (DLCO) 41%, mean survival 20 months. NSIP: 67% male, median age 70 years, FVC 72%, DLCO 43%, mean survival 35 months. COP: 50% male, median age 66 years, FVC 93%, DLCO 77%, mean survival 88 months. Significant treatment-related toxicities occurred in 55% IPF, 20% NSIP und 0% COP patients. 30-days postoperative mortality was 25% in IPF, and 0% in NSIP/COP while rate of radiation pneumonitis was 24% in IPF.Conclusions: LC is a frequent comorbidity in IIP, with a higher incidence and reduced survival in IPF compared to other IIPs. LC treatment is associated with significant toxicity, specifically in IPF. Interdisciplinary evaluation of therapeutic options in IIP patients diagnosed with LC is therefore mandatory.